1999
DOI: 10.1017/s0043174500091979
|View full text |Cite
|
Sign up to set email alerts
|

A serine-to-threonine mutation in linuron-resistantPortulaca oleracea

Abstract: We conducted several experiments on linuron-resistant and -susceptiblePortulaca oleraceaand on atrazine-resistant and -susceptibleChenopodium albumto determine their immediate and long-term responses to photosynthesis-inhibiting herbicides. Several photosynthesis-inhibiting herbicides were used, and O2evolution was measured with a Clark-type O2electrode. Resistance ratios (RRs) forP. oleracea, based on O2evolution inhibition, were 8 and > 6 for linuron and diuron, respectively; > 800 for atrazine; and &g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 39 publications
0
34
0
2
Order By: Relevance
“…This same mutation in some atrazine‐resistant weed species shows supersensitivity (negative cross‐resistance) to other herbicide chemistries such as diuron, which target PS II 4. A Ser 264 Thr substitution in a resistant biotype of Portulaca oleracea L conferred a high level of resistance to triazines and ureas 11. The Val 219 Ile substitution confers resistance to atrazine, diuron, dinoseb, ioxynil and metribuzin in Chlamydomonas reinhardtii Dang and higher plants 4.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…This same mutation in some atrazine‐resistant weed species shows supersensitivity (negative cross‐resistance) to other herbicide chemistries such as diuron, which target PS II 4. A Ser 264 Thr substitution in a resistant biotype of Portulaca oleracea L conferred a high level of resistance to triazines and ureas 11. The Val 219 Ile substitution confers resistance to atrazine, diuron, dinoseb, ioxynil and metribuzin in Chlamydomonas reinhardtii Dang and higher plants 4.…”
Section: Introductionmentioning
confidence: 98%
“…Double and triple mutations in the psb A gene of Chenopodium rubrum L cell cultures showed different cross‐resistance patterns, with the most favorable combination for metribuzin resistance being amino acid exchanges of Val 219 Ile and Ala 251 Val conferring from 1200‐ to 5000‐fold resistance to metribuzin 16. A mutation of Ser 264 Thr in P oleracea conferred 300‐fold resistance to linuron, 400‐fold to atrazine, 20‐fold to terbacil, but no cross‐resistance to bentazone and low negative cross‐resistance to bromoxynil 11, 17…”
Section: Introductionmentioning
confidence: 99%
“…Beuret (1988Beuret ( , 1989) demonstrated that linuron resistance in horseweed was likely not due to a chloroplastic mutation and that resistance of common groundsel to this herbicide may be a result of the slow penetration or rapid metabolization of the chemical. Sequence analysis of the chloroplast D1 protein by Masabni and Zandstra (1999b) showed that linuron-resistant common purslane plants had undergone a serine to threonine substitution at position 264.…”
Section: Resultsmentioning
confidence: 99%
“…However, variant alleles in the psbA gene that codes for the D1 protein confer resistance to this group of herbicides (reviewed by Gronwald, 1994). However, this substitution (Ser-264-Gly) confers negligible resistance to phenyl urea herbicides (Devine and Shukla, 2000), whereas a slight variant, Ser-264-Thr, confers resistance to both triazines and urea herbicides (Masabni and Zandstra, 1999). However, this substitution (Ser-264-Gly) confers negligible resistance to phenyl urea herbicides (Devine and Shukla, 2000), whereas a slight variant, Ser-264-Thr, confers resistance to both triazines and urea herbicides (Masabni and Zandstra, 1999).…”
Section: Resistance To Photosystem II Inhibitorsmentioning
confidence: 99%